The aviator - Mann, Michael; Logan, John; Scorsese, Martin; Warner Bross Pictures; Miramax Films ([Burbank, CA ] : Miramax Film Corp and Warner Bross Pictures, 2005)
Explores the early life of the legendary and eccentric millionaire, movie producer, director, and aviator Howard Hughes. One of the 20th century's most compelling figures, Howard Hughes was a wily industrialist, glamorous movie producer and unstoppable American inventor, but he thought of himself first and foremost as an aviator
Title from title screen
CD 2 is for special features includes the making, the visual effects of the aviator, costuming and scoring and so on
Music by Howard Shore ; edited by Thelma Schoonmaker ; executive producer, Leonardo Dicaprio...[et al.]
Casts : Leonardo Dicaprio, Cate Blanchett, Kate Beckinsale, John C. Reilly, Alec Baldwin, Alan Alda
Keywords: Hughes, Howard, -- 1905-1976 -- Drama; Millionaires -- United States -- Drama; Motion picture producers and directors -- Drama; Air pilots -- United States -- Drama